Pengujian Black Box dengan Teknik Equivalence Partitioning pada Aplikasi Monitoring Pemberian Obat Filariasis Berbasis Android - Maulana, Mohammad Reza; Eko Budi Susanto; Paminto Agung Christianto (STMIK Budi Darma, 2024)
The application of information technology in various sectors, including the health sector, has become a necessity. Dinas Kesehatan (Dinkes) of Pekalongan City uses information technology to support the Pekalongan City Government's vision as a Smart City. One of the main focuses of the Health Department is treating elephantiasis (filariasis). Even though we have implemented a Mass Preventive Medication (Pemberian Obat Pencegahan secara Massal – POPM) program, the mycorrhiza filarial (MF) rate is still above 1%, requiring additional POPM. One of the problems is the monitoring of drug administration by Tenaga Pelaksana Eliminasi (TPE) officers which is not optimal. Therefore, a monitoring mechanism is needed, implemented through an online-based executive dashboard. The data and graphs on the dashboard come from an Android-based recording application installed on the TPE officer's smartphone. Android applications need to be tested to minimize errors or bugs which can be tested using the Black Box method. This research aims to test the system in terms of providing input and output without knowing the details of the code. One technique that can be used in Black Box testing is the Equivalence Partitioning technique, which divides the input into valid and invalid partitions to ensure the results match the test case. The research stages involve determining use cases, criteria, test partitions, creating test data, and test case design. Testing is carried out through test cases that test the login process, inputting drug data, and sending photos as proof of drug consumption. The results show that by testing the seven test cases, the system can be used properly according to the expected scenario. Some recommendations for improvements that are needed are adjustments to the output message to users. In general, the application for monitoring filariasis drug administration has functioned well, under the application design. Evaluation produces recommendations for improvements to improve user experience. This research can become a basis for further development, including thorough testing of the application.